Contribution of Market Orientation, Product Innovation, and Online Marketing to the Marketing Performance of Batik SMEs in Yogyakarta - Azizah, Salwa Nur; Nuvriasari , Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The cornerstones of the Indonesian economy are Micro, Small, and Medium-Sized Enterprises, or MSMEs; Yogyakarta's Batik MSMEs is one of them. The purpose of this study is to investigate how product innovation, market orientation, and internet marketing affect Yogyakarta's Batik MSMEs' marketing performance. Purposive sampling was the method utilized in the sampling, and the sample size consisted of 43 MSMEs in Yogyakarta. Multiple linear regression is used by the data analysis tool. The study's findings demonstrate that: (1) Batik MSMEs in Yogyakarta will do much better in terms of marketing if they have a strong market orientation. (2) Product innovation is not a deciding element in marketing performance since it has no discernible impact on the marketing performance of Batik MSMEs in Yogyakarta. (3) Yogyakarta's Batik MSMEs' marketing performance is not significantly impacted by online marketing.